Abiraterone acetate and prednisone in the pre- and post-docetaxel setting for metastatic castration-resistant prostate cancer: a mono-institutional experience focused on cardiovascular events and their impact on clinical outcomes. (8th January 2018) - Cavo, Alessia; Rubagotti, Alessandra; Zanardi, Elisa; Fabbroni, Chiara; Zinoli, Linda; Di Meglio, Antonio; Arboscello, Eleonora; Bellodi, Andrea; Spallarossa, Paolo; Cattrini, Carlo; Messina, Carlo; Boccardo, Francesco
Background: The aim of this work was to to evaluate the incidence and risk factors of adverse events (AEs), focusing on cardiovascular events (CVEs) and hypokalemia, in patients treated with abiraterone acetate (AA) and prednisone (PDN) outside clinical trials, and their association with survival outcomes. Methods: This was a retrospective cohort study of 105 patients treated from 2011 to 2016. Incidence of AEs was descriptively summarized in the whole cohort and by subgroup (pre- versus post-docetaxel). Multivariable Cox proportional hazards models assessed factors associated with progression-free survival (PFS) and overall survival (OS). Results: Overall, median PFS and OS were 14.9 and 24.6 months, respectively. Prostate-specific antigen (PSA) ⩾ 10 ng/ml ( p = 0.007), Gleason Score >7 ( p = 0.008), Eastern Cooperative Oncology Group (ECOG) performance status (PS)1–2 ( p = 0.002), duration of androgen deprivation therapy (ADT) ⩽ 43.2 months ( p = 0.01), and body mass index (BMI) > 25 ( p = 0.03) were associated with worse PFS; presence of pain ( p = 0.01), ECOG PS1–2 ( p = 0.004), duration of ADT ⩽ 43.2 ( p = 0.05), and BMI > 25 ( p = 0.042) were associated with worse OS. Incidence of CVEs was as follows: hypertension 17.1%, fluid retention 4.8%, cardiac disorders 8.6%. 16.2% of patients developed hypokalemia. Age ⩾ 75 years was associated with higher probability of cardiac disorders ( p = 0.001) and fluid retention ( p = 0.03). CVEs did not impact on PFS or OS. Hypokalemia was associated with better median OS ( p = 0.036). Similar associations were observed after stratification by subgroup. Conclusions: Median PFS and OS estimates and incidence of CVEs and hypokalemia in our series are consistent with those of pivotal trials of AA plus PDN, confirming the efficacy and safety of this regimen also in the real-world setting. Elderly patients have higher odds of developing/worsening CVEs. However, regardless of age, CVEs were not associated with worse outcomes. Treatment-related hypokalemia seemed to be associated with longer OS, albeit this finding needs confirmation within larger, prospective series.